Maine State Law and Legislative Reference Library - Barden, John (Maine Policy Review, 2013)
The Maine State Law and Legislative Reference Library provides reference assistance to legislators, the judiciary, state agencies, members of the bar, and citizens across the state of Maine and beyond from its rich and unique collection of legal and legislative materials.